Comparative study among constrained application protocol extensible messaging and presence protocol of IoT - Abdal Motalib Alshrif; Ashraf A. Gouda; Mohammed A. Razek (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Many specialists are now looking for ways for commercial development and the introduction of technology and internet applications, especially since many homes in smart and developed cities need a great degree of fitness and electrical control. Now, days the Internet of Things shows a most important potential for commercial development in certain sectors. Therefore, this paper came with the aim of revealing a large variety of constantly evolving protocols for the internet of thing network design in particular three of these are constrained protocols such as message queuing telemetry transfer, application protocol message protocol extended, and message queuing telemetry transfer. To achieve this, the researcher used and followed the qualitative approach that relies on survey tools and theoretical presentation. Among the results obtained that: message queuing telemetry transfer is the best protocol among the three types as it has a high degree of reliability using supportive service quality levels and characterized by the use of neutral packets. The information may also contain binary or text content and has a superior transmission mechanism with efficiencies such as one-to-one, many-to-many or one-to-nothing. In addition, and for ease he uses easy-to-state strategies.